Extensive ileocaval and renal vein thrombosis mimicking acute pyelonephritis - Khiste, Saurabh D.; Avinash, Ignatius; Khan, Mohammed F. (International Journal of Research in Medical Sciences, 2023)
Renal vein thrombosis (RVT) is a rare clinical diagnosis which is the presence of thrombus in the major renal veins or its tributaries. Major causes include nephrotic syndrome, trauma, malignancy, hypercoagulable states. Presentation could be unilateral or bilateral flank pain and/or haematuria. Symptoms could be confused with nephrolithiasis. A normal ultrasonography (USG) in the initial stage could delay the diagnosis and hence propensity for dreaded complications such as loss of renal function and pulmonary embolism. Anticoagulation is the mainstay of therapy for RVT. Review of the literature reveals that thrombolytic therapy can also be used in patients with the most severe disease. Here we present a case of a young male, who initially suspected to have acute pyelonephritis, turned out to have extensive Iliocaval and unilateral RVT secondary to factor V leiden mutation who underwent catheter directed thrombolysis and mechanical thrombectomy.